A new protein nucleic‐acid coarse‐grained force field based on the UNRES and NARES‐2P force fields. Issue 28 (11th October 2018) - Sieradzan, Adam K.; Giełdoń, Artur; Yin, Yanping; He, Yi; Scheraga, Harold A.; Liwo, Adam
Abstract : Based on the coarse‐grained UNRES and NARES‐2P models of proteins and nucleic acids, respectively, developed in our laboratory, in this work we have developed a coarse‐grained model of systems containing proteins and nucleic acids. The UNRES and NARES‐2P effective energy functions have been applied to the protein and nucleic‐acid components of a system, respectively, while protein–nucleic‐acid interactions have been described by the respective coarse‐grained potentials developed in our recent work (Yin et al., J. Chem Theory Comput . 2015, 11, 1792). The Debye–Hückel screening has been applied to the electrostatic‐interaction energy between the phosphate groups and charged amino‐acid side chains. The model has been integrated into the UNRES package for coarse‐grained molecular dynamics simulations of proteins and the implementation has been tested for energy conservation in microcanonical molecular dynamics runs and for temperature conservation in canonical molecular dynamics runs. Two case studies were performed: (i) the dynamics of the Ku protein heterodimer bound to DNA, for which it was found that the Ku70/Ku80 protein complex plays an active role in DNA repairing and (ii) conformational changes of the multiple antibiotic resistance (MarA) protein occurring during DNA binding, for which the functionally important motions occurring during this process were identified. © 2018 Wiley Periodicals, Inc. Abstract : Illustration of the coarse‐grained representation of protein–nucleic‐acid systems implemented in this work with the example of the multiple antibiotic resistance (MarA) protein–DNA complex. Left: the DNA fragment in NARES‐2P representation, right: the protein fragment in UNRES representation. The virtual bonds are shown as sticks, united side chains and nucleic‐acid bases are shown as ellipsoids of revolution, united peptide groups are shown as light‐blue spheres and united phosphate groups are shown as light‐red spheres.